Relevance of peripheral blood progenitor cell counts during steady-state hematopoiesis to estimate the number of progenitor cells mobilized following granulocyte colony-stimulating factor-supported chemotherapy - Frühauf, Stefan; Schmitt, K.; Veldwijk, Marlon Romano; Schiedlmeier, Bernhard; Martin, S.; Zeller, W. Jens; Haas, Rainer (Infusion therapy and transfusion medicine, 1999)
Peripheral blood progenitor cells can be mobilized using cytotoxic chemotherapy and cytokines. We were looking for predictive parameters indicating a patient’s response to a given mobilization regimen. Patients and Methods: Flow cytometry analysis and clonogenic assays were used to examine hematopoietic progenitor cells in bone marrow and peripheral blood prior to G-CSF-supported chemotherapy and were compared to CD34+ cell counts in peripheral blood and leukapheresis products in the recovery phase. Stroma-dependent long-term cultures were performed from steady-state bone marrow and leukapheresis product samples. 90 patients (24 non-Hodgkin’s lymphoma, 5 Hodgkin’s disease, 33 multiple myeloma, 28 solid tumor) were included in this study.
Gesehen am 21.01.2022